SYNDROMIC SURVEILLANCE: A POTENTIAL METHOD FOR ALTERNATIVE ANIMAL HEALTH SURVEILLANCE SYSTEM - Kardena, I Made (Buletin Veteriner Udayana, 2012)
Syndromic surveillance is an alternative surveillance system which can potentially detectanimal disease outbreaks in the early stages. Although syndromic surveillance haslimitations for the detection of sub-clinical and specific diseases, the method has the abilityto detect disease outbreaks rapidly including clinical emerging issues. In addition,syndromic surveillance is a suitable surveillance tool that can be applied in developingcountries since it is a low-cost surveillance method and is an option for poorly-resourcedveterinary services.
Keywords: Surveillance, Early stage monitoring, Epidemiology